Gambaran mkroskopis Basil Tahan Asam pada metode Langsung dan metode Sentrifugasi - Safwan, Safwan; Fitriati, Fitriati; Putri, Safridha Kemala; Fitriana, Fitriana (JoMLaT (Journal of Medical Laboratory Technology), 2024)
Acid-Resistant Bacillus (BTA) is another name for Mycobacterium tuberculosis, which is a rod-shaped bacterium that is resistant to acid alcohol washing when staining. BTA causes a contagious and deadly infectious disease commonly called tuberculosis or TB. BTA examination using the direct method is a faster examination compared to the centrifugation method. This research aims to see the differences in microscopic images using the direct method and the centrifugation method. This study used a descriptive method, where the population in this study were all positive (+) sputum specimens, while there were 5 BTA positive (+) specimens. The direct BTA examination method and the centrifugation method used Zeihl Neelsen staining. The results of the study showed that the BTA examination using the direct method had weaknesses in terms of the large amount of mucous tissue and some BTAs were not clearly visible on microscopic observation. Meanwhile, BTA examination uses the centrifugation method with the addition of 4% NaOH which can digest tissue so that BTA is easy to find. Therefore, it can be concluded that the centrifugation method for BTA examination is better than the direct method.